Cost comparison of different models of palliative care delivery. (23rd September 2020) - Comans, Tracy; Nguyen, Kim‐Huong; Stafford‐Bell, Fiona; Agar, Meera
Abstract: Objective: The aim of this project was to assess the value for money of a modified unit within a residential aged care facility (RACF) for people requiring palliative care at the end of life. Methods: A three‐way comparison using a mixed‐method costing was used to estimate the per day cost of the unit compared to care in a palliative care unit within a hospital and a standard RACF bed. Results: The cost of the unit was estimated at 242 per day (2015 Australian dollars). The palliative care hospital bed cost 1, 664 per day. The cost of a standard RACF bed was 123 per day, indicating that an additional 120 per day is required to provide the higher level of care required by people with complex palliative care needs. Conclusion: A modified RACF unit could provide substantial cost savings to the health budget for selected complex palliative care patients.